The Regional Burden of Parkinson’s Disease in Kazakhstan 2014–2021: Insights From National Health Data - Ruslan Akhmedullin; Arnur Gusmanov; Gulnur Zhakhina; Byron Crape; Temirgali Aimyshev; Yuliya Semenova; Gaziz Kyrgyzbay; Abduzhappar Gaipov (Parkinson's Disease)
Conclusion: This study is the first of its kind in Central Asia to examine the burden of PD using a large-scale outpatient registry. The findings underscore the need for targeted interventions to address the growing burden of PD, particularly among males and ethnic Kazakhs. Additionally, further research is needed to explore the inverse association between hypertension and survival in the PD cohort.